Mortalità in una coorte di addetti alla costruzione e riparazione di carrozze ferroviarie in un’azienda di Bologna / Mortality in a cohort of railway rolling stock construction and repair workers in Bologna - Leda Pavone, V.; Scarnato, C.; Marinilli, et al., P. (La Medicina del Lavoro, 2012)
Riassunto Obiettivo: Lo studio ha indagato la mortalità per tutte le cause, in specifico per i tumori asbesto-correlati, in una coorte di operai. Disegno: studio di coorte storico. Metodo: La popolazione comprendeva 1849 lavoratori occupati nel periodo 1960-1986; gli addetti in produzione erano 1704 (92,2%) e gli impiegati 145 (7,8%). La fine del follow-up è stata fissata al 31/12/2008. I RSM sono stati calcolati utilizzando i tassi specifici per età, sesso e periodo dell’Emilia-Romagna. Risultati: La mortalità generale (RSM=1,16; IC95% 1,08-1,25) e quella per tutti i tumori maligni ha superato in modo significativo quella attesa. Sono risultati superiori agli attesi i decessi per tumore maligno della pleura (RSM=24,43; IC95% 17,37-34,37), per tumore del polmone (RSM=1,24 IC95% 1,00-1,53), per tumore del peritoneo (RSM=6,35; IC95% 2,64-15,25) e per tumore della vescica (RSM=1,71; IC95% 1,03-2,84). L’eccesso di mortalità per tumore polmonare è risultato significativo negli esposti per almeno 20 anni (RSM=2,99) e dopo una latenza di 40 anni e oltre (RSM=1,99). Il tumore della pleura è risultato fortemente associato (trend test p<0,0001) alla durata dell’esposizione e alla latenza. Conclusioni: Lo studio ha permesso di identificare un eccesso di mortalità per i tumori amianto-correlati, confermando sia per i tumori maligni della pleura sia per quelli del polmone la relazione positiva con durata e latenza. Summary «Mortality in a cohort of railway rolling stock construction and repair workers in Bologna». Background: A private company in Bologna worked for the Italian State Railways (FS) from 1919 to 1998; since the early ‘60s it used asbestos for new carriage insulation and renovation of carriages already circulating which were entirely spray-coated with asbestos. Objectives: The study aimed to investigate all causes mortality, in particular mortality from asbestos-related neoplasms in blue-collar workers. Methods: The cohort consisted of 1,849 people, active in 1960 or hired in 1960-86: 1,704 (92.2%) blue-collar workers and 145 (7.8%) white-collar workers. The end date of the follow up was established as 31/12/2008. Regional reference mortality rates were used. Results: Mortality from all causes (SMR=1.16; 95%CI 1.08-1.25) and from malignant neoplasms (SMR=1.20; 95%CI 1.06-1.35) significantly exceeded expected rates. In particular, a statistically significant increase was observed for pleural malignant cancer (SMR=24.43; 95%CI 17.37-34.37), lung cancer (SMR=1.24; 95%CI 1.00-1.53), peritoneal cancer (SMR=6.35; 95%CI 2.64-15.25) and bladder cancer (SMR=1.71; 95%CI 1.03-2.84). The excess lung cancer SMR was highly significant after 20 years of exposure and with a latency longer than 40 years. An association between pleural malignant cancer and duration of exposure and latency (trend test p value <0,0001) was observed. Conclusion: This study on a cohort of asbestos-exposed workers showed an increase in lung cancer SMRs by risk that was statistically significant in workers exposed for at least 20 years and after 40 years of latency. The neoplasm of pleura was strongly associated with both duration of exposure and latency.